Exploring the Influences of Social Networking Service (SNS) on Consumer Purchase Behaviour - Nur Anis Shazwani Ahmad Shukri; Norsimaa Mustaffa (USIM Press, 2024)
AL-I’LAM –J. Contemp. Islam. Comm. & Media Vol. 3, Issue 1, July2023 Page (137-155)